Sperm parameters reflect the effects of topical use of Copaifera oil (Copaifera sp.) in Wistar rats (Revista Brasileira de Plantas Medicinais, 2020)
Copaiba resin oil (CO) is used in the treatment of inflammatory skin injuries in humans. This study assessed the effects of topical use of CO ointment on sperm parameters. Sixty-three Wistar male rats were anesthetized and two wounds were inflicted on the back of each rat. The healing injuries were treated daily with petroleum jelly (control group), 0.01%, and 0.1% of CO ointment until the day they were euthanized: seven, fourteen, or twenty-one days later (D7, D14, or D21, respectively). Each group contained seven animals and the traits assessed in terms of sperm quality were sperm motility, integrity of plasma membrane, mitochondrial function, DNA integrity, and histopathological characteristics. Animals treated with CO at 0.01% and 0.1% for D7 had an increase in the number of cells with injured membranes (79.6% and 68.9%, respectively) and nonfunctional mitochondria (44.8% and 48.5%, respectively) when compared to the control group (43% of injured membrane and 19% of nonfunctional mitochondria). After D14 of treatment, we observed an increase (P